Terahertz All-Optical Logic Gates Based on a Graphene Nanoribbon Rectangular Ring Resonator - Wei Su; Zhen Geng (IEEE Photonics Journal)
A type of all-optical logic gates based on a graphene nanoribbon rectangular ring resonator for terahertz frequency is proposed and numerically investigated by finite-difference time-domain simulations. By utilizing the surface plasmon polaritons propagated along the graphene nanoribbon, the tunability in frequency of the filter effect can be achieved by tuning the bias voltage of graphene. The proposed structure can realize NOT, XOR, and XNOR gates, corresponding to the high contrast ratio of about 14.2, 19.5, and 14.1 dB, respectively. The proposed logic gates would be a potential component for designing all-optical logical photonic devices in an optical communication system.